Biodiversity of the Gulf of Guinea Oceanic Islands Science and Conservation - Ceríaco, Luis M. P.; de Lima, Ricardo F.; Melo, Martim; Bell, Rayna C. (Springer Nature, 2022)
This open access book presents a comprehensive synthesis of the biodiversity of the oceanic islands of the Gulf of Guinea, a biodiversity hotspot off the west coast of Central Africa. Written by experts, the book compiles data from a plethora of sources - archives, museums, bibliography, official reports and previously unpublished data - to provide readers with the most updated information about the biological richness of these islands and the conservation issues they face. The Gulf of Guinea Oceanic Islands (Príncipe, São Tomé and Annobón and surrounding islets) present extraordinary levels of endemism across different animal, fungi and plant groups. This very high endemism likely results from the long geological history of the islands and their proximity to the diversity-rich continent. Many researchers, students and conservationists from across the globe are interested in documenting biodiversity on the islands, understanding the evolutionary origins of this diversity, and mitigating the impacts of global change on this unique archipelago. This book aims to be a primer for a broad audience seeking baseline biodiversity information and to serve as a roadmap for future research efforts aiming to fill knowledge gaps in understanding and conserving the unparalleled biodiversity of the Gulf of Guinea islands.